The hand-held fan & the Calming Hand for people with chronic breathlessness: a feasibility trial - Swan, Flavia; Johnson, Miriam (European Respiratory Society, 2025)
Introduction: The battery operated hand-held fan (“fan”) and the Calming Hand (CH), a cognitive strategy, may be helpful for chronic breathlessness. Objective: To test the feasibility of a phase III randomised controlled trial (RCT) evaluating the impact of the fan and/or CH compared with exercise advice alone for the relief of chronic breathlessness due to respiratory conditions. Methods: Single site, feasibility “2x2” factorial, non-blinded, mixed-methods RCT. Participants randomly allocated to four groups: fan + exercise advice vs CH + exercise advice vs fan + CH + exercise advice vs exercise advice alone. Measures included: recruitment, acceptability; data quality and study outcomes (baseline, day 28); modified incremental shuttle walk test (mISWT), recovery time from exertion-induced breathlessness, Life-space, General Self-Efficacy Scale and breathlessness numerical rating scales. Willing participants and carers were interviewed at study end. Results: Recruitment/acceptability/data quality: 53 people were screened, 40 randomised and completed; (mean age 72 years (SD 9.8), 70% male). There were few missing data (2 mISWT). Recovery time [seconds] from exertion-induced breathlessness showed most improvement for the fan; mean reduction from baseline -33.5 vs CH mean increase from baseline 5.7. This represents a recovery speed at day 28 -20.4% faster for the fan vs 4.1% slower for the CH. Qualitative data indicated participants valued the faster recovery and identified the fan as a useful “medical” device, but found the CH unhelpful. Conclusion: A phase III RCT is feasible. Mixed-method data synthesis supports recovery time as a novel, meaningful outcome measure.